Neuron-astrocyte transmitophagy is altered in Alzheimer's disease - Riikka Lampinen; Irina Belaya; Liudmila Saveleva; Jeffrey R. Liddell; Dzhessi Rait; Mikko T. Huuskonen; Raisa Giniatullina; Annika Sorvari; Liisi Soppela; Nikita Mikhailov; Isabella Boccuni; Rashid Giniatullin; et al. (Neurobiology of Disease, 2022)
Under physiological conditions in vivo astrocytes internalize and degrade neuronal mitochondria in a process called transmitophagy. Mitophagy is widely reported to be impaired in neurodegeneration but it is unknown whether and how transmitophagy is altered in Alzheimer's disease (AD). Here we report that the internalization of neuronal mitochondria is significantly increased in astrocytes isolated from AD mouse brains. We also demonstrate that the degradation of neuronal mitochondria by astrocytes is increased in AD mice at the age of 6 months onwards. Furthermore, we demonstrate for the first time a similar phenomenon between human neurons and AD astrocytes, and in murine hippocampi in vivo. The results suggest the involvement of S100a4 in impaired mitochondrial transfer between neurons and AD astrocytes together with significant increases in the mitophagy regulator and reactive oxygen species in aged AD astrocytes. These findings demonstrate altered neuron-supporting functions of AD astrocytes and provide a starting point for studying the molecular mechanisms of transmitophagy in AD.